Trust as a Factor in the Legitimization of the Law in the Digital State - V. V. Denisenko (Теоретическая и прикладная юриспруденция)
The article deals with a complex of issues related to trust in the legal system. The problem of understanding trust from the perspective of various types of understanding of law is revealed. The analysis of trust as a factor of legitimation of law is carried out. The author comes to the conclusion that trust in law allows us to reveal the issues of the effectiveness of the law. Trust in the modern digital state is connected with the principle of deliberation in the process of making public legal decisions.